Voices of the Well-Elderly: A Qualitative Study of Psychological Strengths and Well-Being - Kirkby-Geddes, Emma E; Macaskill, Ann (The Journal of Behavioral Science, 2016)
The aim of this study is to explore positive aspects of ageing. Specifically, examining the psychological strengths of optimism, hope, gratitude, forgiveness and curiosity and focusing on participants' experiences of what is uniquely good about later life in a sample of elderly people living independently in the community. Research on psychological strengths is largely quantitative but this study provides ecological validity to the concept of psychological strengths in well older adults. Using Interpretative Phenomenological Analysis (IPA) eight in-depth individual interviews undertaken with well adults aged between 65 and 85 years old were analyzed. A cross-case analysis identified four major themes and a number of sub-themes: Psychological Strengths (Lay Descriptions of Strengths, Examples of Strengths); Benefits of old age (Choice and Freedoms, Enjoyable activities, Resources); Relationships (Friendships, Family, Self); Attitudes to getting older (Debating the age label, Attitudes informed by media). The psychological strengths of gratitude, curiosity and optimism were very apparent in the narratives while forgiveness was less prevalent and hope was not a character strength used by the participants in their descriptions of ageing. The study addresses the absence of the voices of older adults in research. In addition, this qualitative study augments the existing quantitative evidence base for positive psychology. Keywords: psychological strengths, older adults, well-elderly, qualitative research, Interpretative Phenomenological Analysis